The effect of ICT on energy consumption and economic growth in South Asian economies: An empirical analysis - Usman, Ahmed; Ozturk, Ilhan; Hassan, Ali; Maria Zafar, Syeda; Ullah, Sana (Telematics and informatics, 2021)
•We analyze the effects of ICT on economic performance and energy consumption of selected South Asian economies.•In the long-run, ICT significantly and positively contributed to the economic growth of India only.•India is the only country in South Asia that has achieved energy efficiency as a result of increased use of ICT.•GDP per capita has a positive and significant impact on energy consumption in both Pakistan and India.•South Asian economies try to follow their regional partner, India. This study contributes to the literature by analyzing the effects of information and communication technology (ICT) on economic performance and energy consumption of selected South Asian economies i.e. Bangladesh, India, Pakistan and Sri Lanka for the period of 1990–2018. For empirical analysis, we employed the bounds testing approach of cointegration and error correction modelling. The findings of the study confirm that, in the long-run, ICT significantly and positively contributed to the economic growth of India only. Similarly, India is the only country in South Asia that has achieved energy efficiency as a result of increased use of ICT. However, energy consumption proved to be an important determinant of GDP per capita in India and Pakistan. Also, GDP per capita has a positive and significant impact on energy consumption in both India and Pakistan. These results imply that South Asian economies try to follow their regional partner, India, in increasing the role of ICT in their economies, which on one side will boost their economic growth and on the other side will help them in achieving energy efficiency. Moreover, the energy conservation policy could prove detrimental to South Asian economies.